Dampak Perselisihan Ukraina-Rusia 2022 Terhadap Perekonomian, Inflasi, Perdagangan Internasional di Asia Tenggara - Yosep Yudianto; Didit Supriyadi; Kosasih Kosasih (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2023)
This research is motivated by the problem that the invasion of Ukraine by Russia has become a global event with a significant impact for all countries, which occurred on February 24, 2022. Russia is known as the world's top three producer and exporter of oil, natural gas and coal. On the other hand, Ukraine is known as a guardian of the world business sector exporter of sunflower oil, corn and exporter of wheat, the commodity is in the world's top five. The method used in this study uses a library method or approach, that literature or literature study can be interpreted as a series of activities related to methods of collecting library data, reading and recording and processing research materials. The results of this study indicate that the conflict between Russia and Ukraine will have an impact on the realignment of the international trade system, and countries that have ties with the two countries will have a significant impact on national interests within their own countries. The economic sector will definitely be affected first because of the conflict. global supply chain disruptions, rising costs of food, energy, etc. In addition, fuel prices have risen in a number of countries.